A comparison of community bank failures and FDIC losses in the 1986–92 and 2007–13 banking crises - Balla, Eliana; Mazur, Laurel C.; Prescott, Edward Simpson; Walter, John R. (Journal of Banking & Finance, 2019)
Failures and FDIC losses for community banks during the banking crises of the late 1980s and late 2000s are compared. Despite increases in risky commercial real estate (CRE) lending and more severe economic shocks in the recent crisis, failure rates were lower. We find that other changes in bank characteristics, like higher capital, made community banks more resilient to shocks. In contrast, FDIC losses on failed banks were higher. These are not explained by changes in CRE exposure or economic shocks. We find that an interest-receivable variable is predictive of failures and FDIC losses. Implications for prompt corrective action are discussed.